THE PATHOLOGY OF TRIBAL NATIONALISM ACCORDING TO HANNAH ARENDT: UNCOVERING RELIGIOUS POPULISM MECHANISMS WHICH JEOPARDIZE CULTURAL DIVERSITY - Johannes Haryatmoko (Universitas Gadjah Mada, 2019)
The sustained rise of religious populism across the globe has influenced Indonesian political situation. In Indonesia, the last ten years have witnessed the increasingly widespread emergence of religious populism. Populists express strong moral judgments in decrying corruption, moral decadence and corrupted elite in power. They define society in Manichean terms as divided into a good ‘us’ and an evil ‘them’. In defining both of these categories, they put forward the important role of religious identities in order to classify who fits into the category of ‘us’ and who belongs to ‘them’. Hannah Arendt offers sharp analyses allowing to uncover religious populism mechanism. Her main analysis was based on the pathology of tribal nationalism. The result of her analysis helps us to explore the similarities of tribal nationalism pathology and religious populism phenomena. The use of comparative and critical approaches helps to conclude that the pathology of tribal nationalism gives lessons on how such a movement cannot accept differences and tends to be totalitarian. Such a comparison opens new perspectives on helping to examine the phenomena of propaganda, slandering, intimidation, mass mobilization, persecution, violence, and formations of paramilitary forces as instruments for totalitary movements used by religious populism. Such phenomena are loaded with manipulations and lies which have fragmented social groups and weakened political culture so that ideological consensus is impossible. Ordinary citizens, even the intellectual, are not able to oppose well-organized lies and manipulations. The danger is that such religious populism maneuvres risk jeopardizing the foundation of the Indonesian nation, which is formulated under the motto “unity in diversity”.